(untitled) (Ecological Bulletin of Kryvyi Rih District, 2024)
The article presents the results of assessing the variability of morphometric parameters of silver birch (Betula pendula) leaf blades on the devastated lands of the Petrovsky iron ore dump. The study utilized the results of our own research conducted from 2022 to 2023 on the territory of the Petrovsky dump in the Kryvyi Rih iron ore region. Investigations were carried out on technogenically disturbed areas that had not been reclaimed. It was found that the morphometric parameters of birch leaf blades exhibit clear ecological determinism. On all investigated plots characterized by a high level of pollution, the fluctuating asymmetry for Betula pendula, naturally occurring on the devastated lands of the Petrovsky dump, was determined to be 0.0556, indicating an approximation of the ecological condition to a pre-critical level. After calculating the average values of the integrated FA indicators across all sites, it was established that the most sensitive feature to adverse conditions in devastated lands is the distance between the bases of the first and second-order veins (0.132), while the most stable feature is the second characteristic (length of the second-order vein from the base of the leaf), which is 0.024. Maximum Spearman’s correlation coefficients were recorded between the parameters: gross content of heavy metals in the soil of devastated lands and the level of fluctuating asymmetry in birch leaves (r = 0.800). The study demonstrates that woody plant species on the Petrovsky dump are generally subject to the influence of adverse environmental factors.